Islamic mysticism and interreligious dialogue - Saeedimehr, Mohammad (Poligrafi, 2020)
My aim in this paper is to investigate Islamic Mysticism and find out how and to what extent mystical views can build good grounds for a productive and fruit-ful interreligious dialogue. First, I provide a brief clarification of what I mean by the notions of ‘interreligious dialogue’ and ‘Islamic mysticism.’ Then, I explain three mystical principles as three bases for the promotion of interreligious dialo-gue. These are the metaphysico-theological principle of ‘the unity of existence’ (wa?dat al-wujud), the anthropological thesis of fitra (primordial nature), and the hermeneutic method for interpreting the Qur’an. Finally, I explore the implicati-ons of these principles for interreligious dialogue and discuss the role of mystical teachings in promoting interreligious dialogue in two different, though interrela-ted, areas: doxastic and moral.
Keywords: Ibn ‘Arabi; interreligious dialogue; Islam; Islamic mysticism; islamski misticizem; medreligijski dialog; sufism; sufizem; tujec